Introduction to tissue engineering : applications and challenges - Birla, Ravi (Wiley, 2014)
"Covering a progressive medical field, Tissue Engineering describes the innovative process of regenerating human cells to restore or establish normal function in defective organs. As pioneering individuals look ahead to the possibility of generating entire organ systems, students may turn to this textbook for a comprehensive understanding and preparation for the future of regenerative medicine. This book explains chemical stimulations, the bioengineering of specific organs, and treatment plans for chronic diseases, like diabetes. It is a must-read for tissue engineering students and practitioners"-- Resumé vydavatele
Keywords: tkáňové inženýrství; tissue engineering; učebnice vysokých škol; elektronické knihy; textbooks (higher); electronic books